2020
DOI: 10.4014/jmb.1910.10021
|View full text |Cite
|
Sign up to set email alerts
|

The Endophytic Bacteria Bacillus velezensis Lle-9, Isolated from Lilium leucanthum, Harbors Antifungal Activity and Plant Growth-Promoting Effects

Abstract: Bacillus velezensis is an important plant growth-promoting rhizobacterium with immense potential in agriculture development. In the present study, Bacillus velezensis Lle-9 was isolated from the bulbs of Lilium leucanthum. The isolated strain showed antifungal activities against plant pathogens like Botryosphaeria dothidea, Fusarium oxysporum, Botrytis cinerea and Fusarium fujikuroi. The highest percentage of growth inhibition i.e., 68.56±2.35% was observed against Fusarium oxysporum followed by 63.12 ± 2.83%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 71 publications
1
28
0
Order By: Relevance
“…Rhizosphere bacteria B. subtilis is commonly studied for their strong antifungal activity against a wide range of phytopathogenic fungi such as Rhizoctonia solani, Alternaria alternata, F. oxysporum, Macrophomina phaseolina, and Pythium ultimum (Alamri et al 2012;Wu et al 2019 (Trinh et al 2019). Research by Khan et al (2020) revealed that the endophytic B. velezensis Lle-9 isolated from Lilium leucanthum had a plant growth-promoting effect and antifungal activity against Botrytis cinerea, Fusarium oxysporum, Fusarium fujikuroi, and Botryosphaeria dothidea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rhizosphere bacteria B. subtilis is commonly studied for their strong antifungal activity against a wide range of phytopathogenic fungi such as Rhizoctonia solani, Alternaria alternata, F. oxysporum, Macrophomina phaseolina, and Pythium ultimum (Alamri et al 2012;Wu et al 2019 (Trinh et al 2019). Research by Khan et al (2020) revealed that the endophytic B. velezensis Lle-9 isolated from Lilium leucanthum had a plant growth-promoting effect and antifungal activity against Botrytis cinerea, Fusarium oxysporum, Fusarium fujikuroi, and Botryosphaeria dothidea.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of the morphological characters of bacteria included colony-forming, growth pattern, and Gram-staining as previously described (Wikandari et al 2012;Khan et al 2020). The Gram-staining assay for bacterial cells and spores was performed as described previously (Moyes et al 2009).…”
Section: Bacterial Morphological and Molecular Identificationmentioning
confidence: 99%
“…presence of Rubiadin and other antimicrobial compounds in the bacterial culture can assist in isolating Bacillus velezensis Lle-9's antifungal activity. 64 Marioni et al 65 who investigated the antifungal effects of Rubiadin and RBME on Candida tropicalis confirmed that both compounds reduced biofilm formation and had an antifungal effect as mediated by oxidative and nitrosative stress under irradiation, with a significant increase in endogenous ROS and superoxide dismutase (SOD) activity. Rubiadin, in particular, altered the pro-oxidant-antioxidant balance.…”
Section: Antifungal Activitymentioning
confidence: 97%
“…The presence of Rubiadin and other antimicrobial compounds in the bacterial culture can assist in isolating Bacillus velezensis Lle-9’s antifungal activity. 64 …”
Section: Biological Activities Of Rubiadinmentioning
confidence: 99%
“…Several antifungal compounds, including surfactins ( Grady et al, 2019 ), fengycins ( Adeniji et al, 2019 ), and bacillomycin D ( Luna-Bulbarela et al, 2018 ), exerting control over pathogenic fungi have been identified. B. velezensis is an endophytic species that lives in various parts of plants, mainly in the tissues of roots ( Chen et al, 2019 ), leaves ( Li et al, 2020 ), stems ( Kang et al, 2018 ), and even bulbs ( Khan et al, 2020 ). Many plant endophytes have been reported to protect the host against plant fungal pathogens and increase plant growth and tolerance to environmental stresses, making them suitable biocontrol agents ( Bandara et al, 2006 ; Cho et al, 2007 ; Li et al, 2016 ; Ullah et al, 2019 ).…”
mentioning
confidence: 99%